Journal of a second voyage for the discovery of a north-west passage from the Atlantic to the Pacific : performed in the years 1821- 22-23, in his majesty's ships Fury and Hecla, under the orders of Captain William Edward Parry, R.N., F.R.S., and commander of the expedition. - Parry, William Edward, Sir, 1790-1855. (London : John Murray, 1824)
"Published by authority of the Lords Commissioners of the Admiralty." --t.p. Mode of access: Internet.